Reassessing the mechanics of parasite motility and host-cell invasion - Tardieux, Isabelle; Baum, Jake (The Journal of cell biology, 2016)
The capacity to migrate is fundamental to multicellular and single-celled life. Apicomplexan parasites, an ancient protozoan clade that includes malaria parasites (Plasmodium) and Toxoplasma, achieve remarkable speeds of directional cell movement. This rapidity is achieved via a divergent actomyosin motor system, housed within a narrow compartment that lies underneath the length of the parasite plasma membrane. How this motor functions at a mechanistic level during motility and host cell invasion is a matter of debate. Here, we integrate old and new insights toward refining the current model for the function of this motor with the aim of revitalizing interest in the mechanics of how these deadly pathogens move.